Analisis Beban Kerja Terhadap Kualitas Pelayanan dan Implikasinya pada Kebijakan Rekrutmen Pegawai (Studi pada Direktorat Teknologi Informasi ITB Bandung) - Masitoh, Imas Siti; Mulyani, Sri Rochani; Kosasih (Future Science, 2024)
This research aims to analyze workload, service quality and employee recruitment policy at the ITB Bandung Information Technology Directorate. This study uses a quantitative approach. The sample in this study consisted of 31 respondents. The data analysis used is descriptive analysis and verification analysis using path analysis. The results of the descriptive analysis of workload, service quality, and employee recruitment policies, respondents gave a fairly good assessment towards good, there were still some shortcomings that must be considered for improvement. The results of the verification analysis showed that workload had a significant effect on employee recruitment policies, both directly and through service quality.